STRUCTURAL AND BIOPHYSICAL ANALYSIS OF UBE3A AND PARTNER PROTEIN COMPLEXES - Cowan, Emma (2023)
UBE3A is a human E3 ubiquitin ligase, responsible for the transfer of ubiquitin onto substrates to target them for degradation and other cellular processes. UBE3A has been implicated in a range of neurodevelopmental disorders, most notably Angelman Syndrome, but also Dup15Q syndrome, autism spectrum disorders, and schizotypies. Alongside this, it has also been shown to be involved in the oncogenesis of many different types of cancer, including prostate cancer, small-cell lung cancer, B-cell lymphomas, and most notably HPV-associated oropharyngeal cancer and cervical carcinomas. More recent studies have even shown a role of UBE3A in cardiomyopathies, Alzheimers, and the immune response to HIV, as well as identifying it as part of a diverse range of cellular signalling processes.